A NOVEL WIDE BAND OPEN ENDED AIR GAP RADIAL LINE SLOT ARRAY ANTENNA AT 5.8GHZ FREQUENCY BAND - Imran , Mohd Ibrahim; Tharek, Abdul Rahman (WILEY, 2014)
This paper presents a wide band linearly polarized Beam Squinted Radial Line Slot Array (RLSA) antenna at 5.8 GHz band. The open ended air gap technique was used to broader the bandwidth, reduce the antenna size but maintain the high performance characteristic. The antenna implemented radiating slot design with diameter of 200mm and 1.6mm hybrid FR4 and 8mm open ended air gap for dielectric height. The antenna also successfully fabricated and performed a good result. The measured results show a wide 38% of bandwidth with 16 dBi gain at 5.8Ghz frequency. The beamwidth obtained below 15 degree for E and H plane. The research found a wide band RLSA antenna can be achieved using air gap technique and will be a potential candidate for future point to point application for fixed broadband wireless access.